2D SnSe/Si heterojunction for self-driven broadband photodetectors. (2nd May 2019) - Hao, Lanzhong; Wang, Zegao; Xu, Hanyang; Yan, Keyou; Dong, Shichang; Liu, Hui; Du, Yongjun; Wu, Yupeng; Liu, Yunjie; Dong, Mingdong
Abstract: Van der Waals heterojunctions based on atomically thin 2D materials have opened up new realms in modern semiconductor industry. However, it is still challenging to fabricate large-area ultrathin 2D films. Herein, we successfully fabricate wafer-size 2D SnSe films on Si substrate by magnetron sputtering technique, enabling the formation of SnSe/Si van der Waals (vdWs) heterojunction device. The high-resolution transmission electron microscopy is employed to character the structure of SnSe film and SnSe/Si heterojunction with ideal orthorhombic structure and atomically abrupt interface, respectively. The energy diagram of SnSe/Si heterojunction is constructed, exhibiting similar barrier heights for electron and hole carrier. The SnSe/Si heterojunction shows obvious diode behavior with rectification ratio of ~1.6  ×  10 4, forward current of ~194.5 mA cm −2 at  ±1.0 V. Furthermore, owing to the high crystalline orientation, specific energy-band alignment, as well as the strong built-in electrical field, the SnSe/Si heterojunction illustrates a broadband photodetecting properties with the wavelength ranging from ultraviolet to near-infrared light, showing a high detectivity of 4.4  ×  10 12 cmHz 1/2 W −1, a high responsivity of 566.4 mA mW −1 and an ultrafast response/recovery time of ~1.6/47.7 µ s under zero external bias. This work provides a new strategy for fabrication of low cost 2D optoelectronic devices with high-performance.